VERIFICATION OF THE PROFILE OF PHYSICAL FITNESS RELATIONED TO THE HEALTH OF BEGINNERS' STUDENTS IN THE FIRST PERIOD OF THE PHYSICAL EDUCATION GRADUATION COURSE AT UNIEVANGÉLICA (Fiep Bulletin - online, 2014)
As Rodrigues, 1991, the term "Life Quality" implicates in the harmonic inter-relation of the several factors that mold and differentiate the daily life of the human being. Many factors from the biological, psychological and social-cultural natures, like: physical health, mental health, longevity, job satisfaction, family relations, disposition,  roductiveness, dignity and even spirituality are associated to the term "Life Quality". The main objective of this research was to set out a profile level of Physical Fitness Relationed to Health (PFRH) of the universitary students who went into the first period of the Physical Education graduation, at UniEvangélica. The academics were 40, being 20 women and 20 men. The tests were done when they entered the graduation course and again, one year later. For this, the following tests were done: anthropometric measures using cutaneous folds - 7 folds- of Pollock and Jackson, to estimate the distribution of the body composition, flexibility, with the " Wells' bank" test. Arm strength in 1 minute, abdominal resistance in 1 minute and Test of VO max indirect- test of 12 minutes in the athletics track. 2 From the men's results, on both moments, using the test "t" student, there was a significant difference in 2 PFRH variables. In this way, men showed statistically, bigger values on the second moment (a year later) in the variables: Flexion/Extension-arms (p< 0,010) and Vo2 max (p=0,011). On the others variables there were no important differences. Comparing the women's results on both moments, using the test "t" student, it was noticed a significant difference in 3 PFRH variables. So, women showed, statistically, bigger values on the second moment in the variables: fatness percentile (p
Keywords: Level of Physical aptitude; health and universitary students.